1984
DOI: 10.1021/jm00370a005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological properties of some cyclic phosphotriesters derived from 2'-deoxy-5-fluorouridine

Abstract: The following derivatives of 2'-deoxy-5'-O-1",3",2"-dioxaphosphacyclohex-2" -yluridine 2"-oxide have been synthesised: 5-fluoro (4), 5"-(benzyloxy)-5-methyl (6), 5"-(benzyloxy)-5-fluoro (7), 5"-hydroxy-5-methyl (8), 5-fluoro-5"-hydroxy (9), 5",5"-difluoro-5-methyl (11), and 5,5",5"-trifluoro (12). Compounds 4, 9, and 12 have been evaluated for their inhibitory effects on the growth and metabolism of murine leukemia L1210 cells. Compound 12 was nearly as potent as 2'-deoxy-5-fluorouridine in its inhibitory effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…37 A series of cyclic phosphates of FUdR and thymidine were synthesized and evaluated for cytotoxicity towards murine leukemia L1210 cells. 38…”
Section: Cyclic Alkyl Phosphotriestersmentioning
confidence: 99%
See 1 more Smart Citation
“…37 A series of cyclic phosphates of FUdR and thymidine were synthesized and evaluated for cytotoxicity towards murine leukemia L1210 cells. 38…”
Section: Cyclic Alkyl Phosphotriestersmentioning
confidence: 99%
“…The comparable activity of the cyclic phosphate in the thymidine kinase-de®cient L1210/BdUrd cell line to that of FUdR and FUdR-MP (ID 50 2.42 AE 0.4 mg/ml, 1.75 AE 0.4 mg/ml, and 2.43 AE 0.43 mg/ml, respectively) suggested that the compound was hydrolyzed extracellularly to FUdR, before cellular uptake. 38…”
Section: Cyclic Alkyl Phosphotriestersmentioning
confidence: 99%
“…The straightforward use of simple nucleotides to by-pass the kinase dependence is precluded on account of their poor membrane penetration (Leibman and Heidelberger, 1955;Lichtenstein et al, 1960). However, there has been much interest in the use of masked phosphate esters as membrane-soluble depot forms of the bio-active nucleotides of several chemotherapeutic nucleoside analogues (Hunston et et., 1984;McGUigan et el., 1989a, b;Jones, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, uncharged phosphate triester derivatives of seve~al_c~e':! '!~t~el"a= peutic nucleosides have been investigated as membranesoluble pro-drug forms (Farquhar, 1985;Hunston, 1984;Chawla, 1984;McGuigan, 1989). Here, we report the first application of these strategies to the potent anti-HIV compound AZT.…”
Section: Introductionmentioning
confidence: 98%